Pengembangan Kreativitas Anak Usia Dini Melalui Kegiatan Seni di PAUD - Ayuni Astuti Sanikam (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to analyze the development of early childhood creativity through art activities in Early Childhood Education (PAUD) and to identify the role of learning media in supporting the process. The method used is a literature study by reviewing various scientific sources such as journals and relevant books. The results of the study indicate that art activities such as painting, collage, and finger painting play an important role in enhancing children's creativity, as they provide opportunities for children to explore, imagine, and express their ideas and feelings freely. In addition, the use of varied and engaging learning media has been proven to increase learning interest and support the development of cognitive, motor, and socio-emotional aspects of children. However, in practice, there are still obstacles such as limited learning media and a lack of innovation in learning activities. Therefore, teachers’ creativity is needed in utilizing the surrounding environment as a learning resource to optimize the learning process.